Analysis of fetal growth restriction in pregnancy in subjects attending in an obstetric clinic of a tertiary care teaching hospital - Seal, Ashish; Dasgupta, Arup; Sengupta, Mousumi; Dastider, Rinini; Sen, Sukanta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Intrauterine growth restriction (IUGR) is defined as fetal growth less than the normal growth potential of a specific infant because of genetic or environmental factors. Fetal growth restriction or intrauterine growth restriction is one of the leading causes of perinatal mortality and morbidity in newborns. Fetal growth restriction is a complex multifactorial condition resulting from several fetal and maternal disorders. Objective of present study was to find out incidence of IUGR and assessment and evaluation of different important changes in IUGR. Methods: Women who attended the Obstetric OPD in their 1st trimester of pregnancy and those who were thought would be able to visit the antenatal clinic for their fortnightly check-up regularly were screened for intrauterine foetal growth retardation. Women with irregular and uncertain menstrual history and where the 1st trimester USG foetal crown rump length did not corroborate with the menstrual gestational age were excluded from this study. Results: Incidence of IUGR was 18.2% and 84% were found to be asymmetrical. IUGR was found to be double among primigravids and women above 30 years. It had been observed that IUGR was associated with certain conditions like short stature (52%), pregnancy induced hypertension (24%) and anaemia (12%). Conclusions: Thus, early USG screening along with robust screening for maternal BMI, nutritional status, and anaemia can assist the obstetric team in providing early diagnosis, prompt intervention, and better outcome in pregnancy with fetal growth restriction.